Adult Langerhans cell histiocytosis and sclerosing cholangitis: a case report and review of the literature - ŞENTÜRK, HAKAN; HATEMİ, Ali İbrahim; Baysal, Birol; Senturk, HAKAN; Behzatoglu, Kemal; Bozkurt, Erol Rustu; Ozbay, Gulsen (My University, 2010)
Sclerosing cholangitis is a rare complication of Langerhans cell histiocytosis in children which can result in liver failure. This combination is even rarer in adults.